Charting the therapeutic landscape: a comprehensive evidence map on medical cannabis for health outcomes - Montagner, Patrícia; de Salas Quiroga, Adán; Ferreira, Arthur Schveitzer; Duarte da Luz, Barbara Marinho; Ruppelt, Bettina Monika; Schlechta Portella, Caio Fabio; Abdala, Carmen Verônica Mendes; Tabach, Ricardo; Ghelman, Ricardo; Blesching, Uwe; Perfeito, João Paulo Silvério; Schveitzer, Mariana Cabral (Frontiers in Pharmacology, 2024)
The therapeutic potential of medical cannabis has garnered significant attention in recent years, prompting an urgent need for a comprehensive understanding of its effectiveness across various health outcomes. This article presents an Evidence Map that systematically summarizes clinical evidence on the use of medical cannabis, including the health conditions it addresses, the interventions employed, and the resulting clinical outcomes. The objective is to map the effectiveness of medical cannabis in relation to a wide range of health outcomes. The systematic review process involved two independent, blinded literature researchers who screened the search output using Rayyan software. For studies deemed relevant, full texts were obtained to clarify inclusion or exclusion criteria, and any disagreements were resolved through group discussion. Out of 1,840 initial references, 279 potential studies were selected and read in full, resulting in the inclusion of 194 studies in this evidence map.